Factors impacting stone-free rate after retrograde intrarenal surgery for calyceal diverticular calculi - Chatporn Boonyapalanant (2020)
© 2020 Boonyapalanant et al. Objective: To evaluate the outcomes of retrograde intrarenal surgery (RIRS) treatment of calyceal diverticular calculi and identify the associated factors affecting post-operative stone-free rate. Materials and Methods: From August 2015 to May 2019, data of 32 patients with calyceal diverticular calculi who were treated by RIRS in a Siriraj Hospital were retrospectively studied. All operations were performed by the same surgeon using flexible ureterorenoscopy (f-URS) and holmium YAG laser lithotripsy. Calyceal diverticula were identified by our refluxing technique and from the collected demographic, diverticular and stone data. Operative outcomes were retrospectively evaluated. Data were analysed to identify the factors associated with stone-free outcomes. Stone-free was defined as no residual stones remaining after surgery. Results: Mean age of the patients was 55.7 years. Stone locations were non-lower pole in 81.2% of cases and lower pole for the remaining 18.8% of cases. Median stone size was 1.2 cm with three as the median number of stones per patient. Calcium oxalate was the most common stone composition (56.3%). Positions of the diverticulum were anterior calyx (34.4%) and posterior calyx (50%), while the remainder were undetermined (incomplete data). Average length of the diverticular neck was 0.4 cm. Mean operative time was 46 minutes and mean hospital stay was 2.9 days. Complications included fever in three patients (9.3%) and sepsis in two patients (6.3%), with overall post-operative stone-free rate at 75%. Factors significantly affecting stone-free status were stone size (P=0.003) and length of diverticular neck (P=0.038). Multivariate analysis determined that only stone size had a statistically significant effect on post-operative stone-free status (P=0.015). Cut off point for stone size that increased the chances of a post-operative stone-free outcome was less than 1.5 cm, as determined by the ROC curve. Conclusion: RIRS was found to be an effective and safe treatment option for the removal of calyceal diverticular calculi. Stone size of less than 1.5 cm offered a better chance of post-operative stone-free condition.